Pengaruh Perlakuan Akuntansi Aktiva Tetap Terhadap Kewajaran Pelaporan Keuangan Pada CV. Sinar Krida Marisa - Masiaga, Novaliastuti (Gorontalo Accounting Journal, 2018)
This study aims to determine how much influence the accounting treatment of fixed assets to the fairness of the financial reporting on the CV. Activities of Marisa beam either simultaneously (together) or partially (on their own). Data collection method used in this research is observation, documentation, questionnaires and interviews, while the basic information gathering that is through a list of questions that tested through validity and reliability test every item questions in the questionnaire. The analytical method used is by using multiple regression formula, Person Product Moment Correlation, test statistics T to see the relation variable X with variable Y is Partial, and Test Statistic F to see the relationships variables X and Y simultaneously.            The object of this research is the accounting treatment of fixed assets and fairness of financial reporting, research conducted locations located Cv. Activities of Marisa rays. The first hypothesis testing results show that the accounting treatment of fixed assets have a significant effect, amounted to 0.614 or 61.4%, while 38.6% is determined by other variables not examined. The second hypothesis testing results in partial accounting treatment of fixed assets include valuation of fixed assets (X1) has a very strong relationship, significant and not the direction of -0.096 or - 96% and Partially accounting treatment of fixed assets includes the cost (X2) have a relationship strong, significant and direction of 0.0767 or 76.7%.